BIOETANOL SERBUK KAYU SENGON (Paraserianthes falcataria (L.) Nielsen) DALAM RANGKA ENERGI ALTERNATIF TERBARUKAN - Briyandika Pratama; Noor Mirad Sari; Yuniarti Yuniarti (Universitas Lambung Mangkurat, 2021)
The purpose of this study is to analyze the volume volume of bioethanol and ethanol content produced from sengon wood powder waste. The method used is factorial RAL 3 x 3 x 3 using data analysis according to the Kolmogorov-Smirnof procedure. Based on the results obtained from measuring the volume of bioethanol from fermentation of sengon sawdust waste (Paraserianthes falcataria (L.) Nielsen), the highest volume was found in the A3B1 treatment of 11.091 ml with the highest average value of 9.006 ml and the lowest volume in the A1B1 treatment combination. amounting to 5,243 ml with the lowest average value of 8.191 ml. The bioethanol content of fermented sawdust from sengon wood sawdust ranged from 7.185% - 9.896% with the combination of A1B2 treatment having the lowest bioethanol content value and the combination of A3B1 treatment had the highest bioethanol content value so that the highest average value was 9.261% and an average value the lowest was 8,690%.Keywords : Bioethanol; Sengon Wood; Bioethanol Volume; Bioethanol Content